Awareness Level of Poultry Husbandry Practices by the Poultry Farmers in Imphal West District of Manipur - Paonam, Manglemba; Ram, Daya (Indian Journal of Extension Education, 2015)
Considerable number of poultry farms has grown up in Imphal west district of Manipur. Hence, the knowledge of poultry  practices occupiers the importance. The present study was conducted in Imphal- West District of Manipur on 120 poultry  farmers selected by multi-stage sampling procedure. The study concluded that a majority of the farmers had medium  level of knowledge on different aspects of poultry production practices. Education, annual income, socio-economic  status, flock size, extension contact, utilization of mass media and attitude toward poultry rearing were the important  factors which have contributed to the knowledge gained by the poultry farmers.
Keywords: Housing; brooding; feeding; watering; vaccination practices & scientific equipments